Treatment time and learning curve analysis of 1.5 T MR-Linac workflows led by radiation oncologists or therapists - J.M. Westerhoff; F.J. Raaijmakers; L.A. Daamen; E.N. de Groot-van Breugel; L.T.C. Meijers; J.R.N. van der Voort van Zyp; J.J.C. Verhoeff; S. Mook; H.M. Verkooijen; M.P.W. Intven (Clinical and Translational Radiation Oncology)
Background and purpose: This study assessed the treatment time of online adaptive (i.e. Adapt-to-Shape, ATS) and virtual couch shift (i.e. Adapt-to-Position, ATP) magnetic resonance guided radiotherapy (MRgRT) on a 1.5 Tesla MR-Linac. Additionally, the transition from a radiation oncologists (RO)-led to a radiation therapist (RTT)-led workflow, and the presence of a learning curve were assessed. Materials and methods: This study was conducted utilizing the prospective Multi-OutcoMe EvaluatioN of radiation Therapy Using the MR-Linac study (MOMENTUM, NCT04075305). Mean (±standard deviation) online adaptation time and total treatment time were collected from MR-Linac log files. Learning and proficiency phases were defined using a cumulative sum (CUSUM) analysis. Independent T-tests were performed. A p-value < 0.01 was considered statistically significant. Results: In total, 4942 fractions of 645 patients were included. Mean total treatment time was 39 (±7), 15 (±2), 34 (±8), 41 (±11), and 40 (±7) minutes for ATS-treated prostate cancer, ATP-treated prostate cancer, ATS-treated pelvic lymph node metstasis (LNM), ATS-treated abdominal LNM and ATS-treated rectal cancer, respectively. Mean online adaptation time of RO-led and RTT-led treatment was 28 (±6) and 25 (±6) minutes (p < 0.001) for ATS-treated prostate cancer. No significant differences in the remaining subgroups were found. In subgroups with a learning curve, mean online adaptation time of learning and proficiency phase were 30 (±6) and 26 (±5) minutes (p < 0.001) for ATS-treated prostate cancer, 27 (±8) and 19 (±7) minutes for pelvic LNM (p < 0.001), and 29 (±7) and 25 (±7) minutes (p < 0.001) for rectal cancer, respectively. Conclusion: The transition from RO-led to RTT-led workflows did not significantly increase total treatment time. The online adaptation time reduced after a learning curve for ATS-treated prostate cancer, pelvic LNM and rectal cancer.Keywords; MRgRT, MR-Linac, time, prostate cancer, oligolymphnode metastasis, rectal cancer.